2014
DOI: 10.1038/srep05049
|View full text |Cite
|
Sign up to set email alerts
|

Direct fabrication of graphene on SiO2 enabled by thin film stress engineering

Abstract: We demonstrate direct production of graphene on SiO2 by CVD growth of graphene at the interface between a Ni film and the SiO2 substrate, followed by dry mechanical delamination of the Ni using adhesive tape. This result is enabled by understanding of the competition between stress evolution and microstructure development upon annealing of the Ni prior to the graphene growth step. When the Ni film remains adherent after graphene growth, the balance between residual stress and adhesion governs the ability to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…By this approach, authors showed that graphene grown at the Ni/SiO 2 interface can be directly retained on a clean silicon dioxide substrate by mechanical removal of the nickel or by in situ delamination of the nickel at high temperature. Importantly, this process eliminates the need for an additional step to transfer graphene from the metal catalyst film to the substrate and resulted in greater than 90% coverage across centimeter-scale dimensions [163]. To achieve large, high-quality single crystals of graphene, Hao and coworkers used the CVD method to grown graphene on cooper (Cu) by a controlled oxygen (O) surface.…”
Section: Future Perspectivementioning
confidence: 99%
“…By this approach, authors showed that graphene grown at the Ni/SiO 2 interface can be directly retained on a clean silicon dioxide substrate by mechanical removal of the nickel or by in situ delamination of the nickel at high temperature. Importantly, this process eliminates the need for an additional step to transfer graphene from the metal catalyst film to the substrate and resulted in greater than 90% coverage across centimeter-scale dimensions [163]. To achieve large, high-quality single crystals of graphene, Hao and coworkers used the CVD method to grown graphene on cooper (Cu) by a controlled oxygen (O) surface.…”
Section: Future Perspectivementioning
confidence: 99%
“…Hart et al [109] successfully produced graphene on SiO 2 /Si substrate using cold-wall CVD. In this study, Ni and SiO 2 are stacked together prior to graphene growth.…”
Section: Catalytic Property Carbon Solubility and Substrate Affinitymentioning
confidence: 99%
“…They also demonstrated that as-synthesized graphene films could be transferred to other substrates (Figure 1b and c). To meet some special requirements, non-metal materials, such as Si [14,15], SiO 2 [26][27][28], BN [29,30] and Si 3 N 4 [31,32], were also used as substrates. However, the non-metal substrates showed the drawback limitations including slow growth rate and discontinuous size.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%